2018
DOI: 10.1371/journal.pone.0207241
|View full text |Cite
|
Sign up to set email alerts
|

Solid peripheral tumor leads to systemic inflammation, astrocyte activation and signs of behavioral despair in mice

Abstract: Prevalence of depression is higher in patients with cancer than in the general population. Sustained systemic inflammation has been associated with depressive behavior and it has been reported that depressed patients commonly display alterations in their immune system. We previously showed that cancer in mice induces a systemic environment that promotes neutrophil activation and leukocytosis. We thus hypothesized that the peripheral systemic response to a solid tumor leads to endothelial activation, which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
7
2
Order By: Relevance
“…However, brain metastasis often starts with endothelial cell activation. A recent study suggested that solid tumors changed the microenvironment and resulted in system inflammation ( 9 ). The induction of various inflammatory factors such as vascular endothelial growth factor C (VEGFC) could mediate endothelial cell activation during colorectal cancer invasion ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, brain metastasis often starts with endothelial cell activation. A recent study suggested that solid tumors changed the microenvironment and resulted in system inflammation ( 9 ). The induction of various inflammatory factors such as vascular endothelial growth factor C (VEGFC) could mediate endothelial cell activation during colorectal cancer invasion ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tumour‐induced peripheral inflammation was also shown to induce astrogliosis in the brains of mice bearing Lewis lung carcinoma (Demers et al, 2018). Astrocytes are intimately linked with endothelial cells of the BBB via the direct contact of astrocyte endfeet with pericyte cells that wrap around CNS vasculature.…”
Section: Blood–brain Barriermentioning
confidence: 99%
“…Therefore, astrocytes are acutely tuned to sense changes in BBB permeability (Heithoff et al, 2021), although the exact contribution of astrocytes to the maintenance of BBB integrity remains disputed (Kubotera et al, 2019). Demers et al (2018) evaluated BBB integrity and observed increased accumulation of fibrin levels around cerebral vasculature and subsequent endothelial cell activation, potentially via endothelial granule release of von Willebrand factor (VWF) (Demers et al, 2018). More recently, in a mouse model of pancreatic ductal adenocarcinoma, increased circulating immune cell infiltration was observed in conjunction with extensive neuroinflammation and cancer‐associated cachexia (Burfeind, Zhu, Norgard, Levasseur, Huisman, Buenafe, et al, 2020a).…”
Section: Blood–brain Barriermentioning
confidence: 99%
“…Based on the role of astrocytes in mediating neuroinflammation and maintaining BBB integrity, astrocyte involvement in CRCI is plausible yet pre-clinical evidence in chemotherapy-treated rodents and non-CNS tumor-bearing rodents is limited. Demers et al found that systemic inflammation including elevated levels of plasma IL-6 and blood neutrophils in a subcutaneous model of Lewis lung carcinoma in C57BL/6 mice was associated with an increase in astrocyte activation and fibrin accumulation in the blood vessels of the brains of tumor-bearing mice compared to controls, however there was no significant change in BBB integrity at 17 days posttransplantation 84 . Gibson et al demonstrated that microglia activation induced by MTX exposure in C57BL/6 mice, increased astrocyte reactivity which was associated with neuronal and oligodendrocyte cell death, and impaired oligodendroglial differentiation 85 .…”
Section: Neuroinflammationmentioning
confidence: 99%